Vortex Shedding Lock-In due to Pitching Oscillation of a Wind Turbine Blade Section at High Angles of Attack. (11th March 2019) - Meskell, Craig; Pellegrino, Alberto
Abstract : The unsteady flow around a pitching two-dimensional airfoil section (NREL S809) has been simulated using unsteady RANS with the transition SST turbulence model. This geometry is chosen to represent a wind turbine blade in a standstill configuration. The Reynolds number isRe = 10 6 based on a chord length of 1 m. A prescribed sinusoidal pitching motion has been applied at a fixed amplitude of7 ° for a range of high angles of attack30 ° < α < 150 ° . At these incidences, the airfoil will behave more like a bluff body and may experience periodic vortex shedding. It is well known that, in bluff body flows, oscillations can lead to a lock-in (lock-in) of the vortex shedding frequency, f v, with the body's motion frequency, f p . In order to investigate the susceptibility of airfoil to lock-in, the frequency ratior (r = f p / f v 0 ) has been varied aroundr = 1 . The lock-in region boundaries have been proposed, and an analysis of the effect of the oscillation amplitude has been conducted. The lock-in map obtained suggests that, for the vibration amplitude considered, the risk of vortex-induced vibration is more significant in the regions ofα ≈ 40 ° andα ≈ 140 °, i.e., for shallower characteristic lengths. Finally, a lumped parameter wake oscillator model has been proposed for pitching airfoils. This simple model is in qualitative agreement with the CFD results.